HUBUNGAN PENGETAHUAN, SIKAP DAN PERILAKU MASYARAKAT TERHADAP KASUS DEMAM BERDARAH DENGUE DI DESA ULEE TANOH KECAMATAN TANAH PASIR KABUPATEN ACEH UTARA - Zurriyani Zurriyani; Eva Mardalena (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Dengue hemorrhagic fever (DHF) is one of infectious diseases in the world that can cause death. Public knowledge about DHF is very important so that it allows the emergence of community attitudes and behaviors related to prevention efforts that can reduce cases and mortality rates due to DHF. The purpose of this study was to determine the relationship of knowledge, attitudes and behavior of the community toward dengue fever cases in Ulee Tanoh Village, Tanah Pasir District, North Aceh Regency in 2020. This research was conducted using descriptive analytic research method with cross sectional approach. The sample used was 149 respondents. Data were analyzed based on Chi-square test. According to the Chi-square test results, it was found that there are 3 respondents family (2.0%) experienced with DHF. The data analysis showed that there was a relationship between community knowledge and dengue cases in Ulee Tanoh Village, Tanah Pasir District, North Aceh Regency with a P value of 0.024 (P 0.05). However, there was no corerelation between community attitudes and DHF cases in Ulee Tanoh Village, Tanah Pasir District, North Aceh Regency with a P value of 0.802 (P 0.05). On the other hand, the results showed there was correlation between community behavior with DHF cases in Ulee Tanoh Village, Tanah Pasir District, North Aceh District with a P value of 0,000 (P 0.05).Keywords: Knowledge, attitudes, behavior